Current Physical Activity Is Independently Associated With Cortical Bone Size and Bone Strength in Elderly Swedish Women. (24th October 2016) - Nilsson, Martin; Sundh, Daniel; Mellström, Dan; Lorentzon, Mattias
ABSTRACT: Physical activity is believed to have the greatest effect on the skeleton if exerted early in life, but whether or not possible benefits of physical activity on bone microstructure or geometry remain at old age has not been investigated in women. The aim of this study was to investigate if physical activity during skeletal growth and young adulthood or at old age was associated with cortical geometry and trabecular microarchitecture in weight‐bearing and non–weight‐bearing bone, and areal bone mineral density (aBMD) in elderly women. In this population‐based cross‐sectional study 1013 women, 78.2 ± 1.6 (mean ± SD) years old, were included. Using high‐resolution 3D pQCT (XtremeCT), cortical cross‐sectional area (Ct.CSA), cortical thickness (Ct.Th), cortical periosteal perimeter (Ct.Pm), volumetric cortical bone density (D.Ct), trabecular bone volume fraction (BV/TV), trabecular number (Tb.N), trabecular thickness (Tb.Th), and trabecular separation (Tb.Sp) were measured at the distal (14% level) and ultra‐distal tibia and radius, respectively. aBMD was assessed using DXA (Hologic Discovery A) of the spine and hip. A standardized questionnaire was used to collect information about previous exercise and the Physical Activity Scale for the Elderly (PASE) was used for current physical activity. A linear regression model (including levels of exercise during skeletal growth and young adulthood [10 to 30 years of age], PASE score, and covariates) revealed that level of current physical activity was independently associated with Ct.CSA (β = 0.18, p < 0.001) and Ct.Th (β = 0.15, p < 0.001) at the distal tibia, Tb.Th (β = 0.11, p < 0.001) and BV/TV (β = 0.10, p = 0.001) at the ultra‐distal tibia, and total hip aBMD (β = 0.10, p < 0.001). Current physical activity was independently associated with cortical bone size, in terms of thicker cortex but not larger periosteal circumference, and higher bone strength at the distal tibia on elderly women, indicating that physical activity at old age may decrease cortical bone loss in weight‐bearing bone in elderly women. © 2016 American Society for Bone and Mineral Research.